Mapping QTL for resistance to new virulent races of wheat stripe rust from two Argentinean wheat cultivars - Cobo, Nicolás; Pfluger, Laura Alicia; Chen, Xianming; Dubcovsky, Jorge (Crop Science Society of America, 2018)
During the last two decades, new virulent and aggressive races of Puccinia striiformis Westend. f. sp. tritici (Pst) have spread worldwide, causing devastating epidemics and prompting the search for new sources of resistance in wheat (Triticum aestivum L.). Between 2012 and 2017, we mapped four stripe rust resistance quantitative trait loci (QTL) effective against the Pst races present in California, USA, using recombinant inbred lines (RILs) developed from the cross between the Argentinean cultivars ‘Klein Proteo’ and ‘Klein Chajá’. The RIL population showed transgressive segregation in all six growing seasons relative to the parental lines, which showed moderate levels of Pst resistance. Analyses by year detected QTL conferring adult plant resistance on chromosomes 1BL, 2BS, 3D centromeric (from Klein Chajá), and 4DL (from Klein Proteo). QYr.ucw-1BL, mapped in the Yr29 resistance gene region, was significant in all seasons (P < 0.01) and explained on average 31.0 to 32.8% of the observed variation. QYr.ucw-2BS showed a stronger effect than QYr.ucw-1BL in 2013 but was ineffective in 2014 and 2016. This QTL also conferred seedling resistance, suggesting that it is an all-stage resistance gene. Centromeric QYr.ucw-3D and QYr.ucw-4DL showed smaller effects than the previous QTL and were significant only in some of the experiments. No significant interactions were detected among QTL, indicating the absence of digenic epistatic effects. The molecular markers identified in this study can be used to combine these genes and accelerate their deployment in wheat breeding programs.